2011
DOI: 10.1007/s11771-011-0702-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative similarity assessment of non-linear chemical fingerprint of traditional Chinese medicine by similarity system theory

Abstract: The similarities of the non-linear chemical (NLC) fingerprints of Radix Glycyrrhizaes from four producing areas and eight other traditional Chinese medicines (TCMs) were calculated, using a systemic similarity calculation method proposed and three other main calculation ones (Euclidean distance, correlation coefficient and included angle cosine). All of the correlation coefficient similarities of different TCMs are higher than 0.952, and the included angle cosines are all higher than 0.962. So, both the correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Process of a nonlinear chemical reaction is very complicated and involves oxidation–reduction reaction, precipitation reaction, neutralization reaction and free radical reaction [ 23 ]. In this study, the mechanism of B–Z oscillatory reaction to use Mn 2+ , , H + , acetone and glucose as the reaction substrates was discussed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Process of a nonlinear chemical reaction is very complicated and involves oxidation–reduction reaction, precipitation reaction, neutralization reaction and free radical reaction [ 23 ]. In this study, the mechanism of B–Z oscillatory reaction to use Mn 2+ , , H + , acetone and glucose as the reaction substrates was discussed.…”
Section: Resultsmentioning
confidence: 99%
“…1 that the essential characteristic information of nonlinear chemical fingerprint mainly included inductive time ( t ind ), undulatory period ( τ und ), undulatory life ( t und ), canyon potential ( E can ), canyon time ( t can ), peak top potential ( E pet ), peak top time ( t pet ), oscillatory start potential ( E uns ), oscillatory end potential ( E une ), oscillatory end time ( t uns ), maximum amplitude ( ΔE max ), which were defined as quantitative information. All of them were described in detail in the literature [ 22 , 23 ]. The researchers [ 23 ] pointed that oscillation wave shape of fingerprint could reflect the characteristics of complex samples, and inductive time, oscillatory life, oscillatory period and oscillatory curve were holistic quantitative information on chemistry components of samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear chemical fingerprint contained abundant qualitative and quantitative information due to its dynamic property. In this study, nonlinear chemical fingerprint (Figure 1) was obtained by adding 1g of pure milk powder into the reactor, which obviously showed that the essential characteristic information of nonlinear chemical fingerprint mainly included undulatory period ( und τ ), undulatory life ( und t ), inductive time ( ind t ), canyon potential ( can E ), canyon time ( can t ), peak top potential ( pet E ), peak top time ( pet t ), oscillatory end potential ( une E ), oscillatory start potential ( uns E ), maximum amplitude ( max E ∆ ), oscillatory end time ( uns t ), which were reported in details in other studies [22]. Oscillation wave shape of fingerprint reflects characteristics of complex samples, and quantitative information is of vital importance for distinguishing and evaluating milk powder.…”
Section: Essential Information Of Nonlinear Chemical Fingerprint Of Mmentioning
confidence: 71%
“…Oscillation wave shape of fingerprint reflects characteristics of complex samples, and quantitative information is of vital importance for distinguishing and evaluating milk powder. Therefore, inductive curve, oscillatory curve, oscillatory-end curve and a part of the equilibrium curve constituted the whole nonlinear chemical fingerprint [22].…”
Section: Essential Information Of Nonlinear Chemical Fingerprint Of Mmentioning
confidence: 99%